Microbial community assessment of mealworm larvae (Tenebrio molitor) and grasshoppers (Locusta migratoria migratorioides) sold for human consumption. (February 2016) - Stoops, J.; Crauwels, S.; Waud, M.; Claes, J.; Lievens, B.; Van Campenhout, L.
Abstract: In Western countries, the popularity of edible insects as an alternative animal protein source is increasing. Nevertheless, there is a lack of profound insight into the microbial safety and shelf life of living insects sold for human consumption. The purpose of this study was to characterise the microflora of fresh edible mealworm larvae and grasshoppers in a quantitative and qualitative way. Therefore, culture-dependent analyses (the total viable aerobic count, Enterobacteriaceae, lactic acid bacteria, yeasts and moulds, and bacterial endospores) and next-generation sequencing (454amplicon pyrosequencing) were performed. High microbial counts were obtained for both insect species. Different insect batches resulted in quite similar microbial numbers, except for bacterial endospores. However, the bacterial community composition differed between both insect species. The most abundant operational taxonomic unit in mealworm larvae was Propionibacterium . Also members of the genera Haemophilus, Staphylococcus and Clostridium were found. Grasshoppers were mainly dominated by Weissella, Lactococcus and Yersinia / Rahnella . Overall, a variety of potential spoilage bacteria and food pathogens were characterised. The results of this study suggest that a processing step with a microbiocidal effect is required to avoid or minimize risks involved with the consumption of edible insects. Highlights: Culture-dependent and independent analyses were used to assess microbial community. Different insect batches and insect species resulted in similar microbial counts. The microbial community composition depended on the insect species. A processing step with a microbiocidal effect is required before consumption.